Body image-related cognitive fusion as a main mediational process between body-related experiences and women's quality of life - Ferreira, C. (2015)
Ferreira, C., & Trindade, I.A. (2015). Body image-related cognitive fusion as a main mediational process between body-related experiences and women's quality of life. Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity, 20 (1), 91-97. doi: 10.1007/s40519-014-0155-y.